DESEMPENHO TÉRMICO NO INVERNO DOS ATUAIS MICROAPARTAMENTOS DE PLANTA LIVRE EM SÃO PAULO. - Leme, Carolina Carvalho; Monteiro, Leonardo M. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper presents a research about thermal performance of the recent production of open plan micro-apartments in São Paulo, during the winter season. The object of this research are open plan micro-apartments smaller than 45m² built between 2011 and 2015. The high representativeness of the micro-apartments in the current real estate market emphasizes the social and cultural transformations, and the occupation of land in the denser areas in the city, therefore highlighting the importance of studies focused on these new dwelling models.